PERKEMBANGAN DAN DIVERSIFIKASI EKSPOR INDONESIA - Hermanto Siregar; Arief Daryanto (School of Business, Bogor Agricultural University (SB-IPB), 2005)
To some extent there was a change of Indonesia’s export in term of product diversification and countries of destination. From the market side , however, there was no change at the composition of nine biggest export destination in the period of 2002-2004. This shows that there was sluggishness in making adjustment and overcoming constraints in trade. Indonesia needs to diversify the market dan the export products further. Foreign direct investment factor per se can not push the diversification. This factor need to be accompanied by economic stability, as well as taking care of the various internal and external constraints.